Rapid Decline in the Uptake Interests for Different SARS CoV-2 Vaccination Doses Over the Post Vaccination Period in Different European Community Countries - Bhatia, Sudhir (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
During the corona virus pandemic outbreak, there are a number of vaccinations approved. They are distributed and used in human beings worldwide. Aim of this study is to analyze the changes in pattern of uptake mood during different dose courses in EU /EEA population. Therefore, there was use of the following methods: The data from official European community website was collected and analyzed with the software for total number of doses distributed and total number of doses applied. Similarly, cumulative percentage of uptake of vaccine from primary course, first booster, second booster and third booster were compared. Results are showing that there is difference of around 0.5 billion doses between the doses distributed and doses used. The uptake interest decreased from primary dose to third booster dose from 85% to 0% among the countries over the time. The conclusion was found as follows: there are discrepancies between the total number of doses distributed and used. There is very strong loss of uptake interest in the populations in EU/EEA with different dose courses. One must study the reasons for such a strong loss of uptake interest and economic losses caused leading to burden on the tax payers.